Menstrual Pattern and Common Menstrual Disorders among Adolescent Girls - Sughra Abbasi, Samina Naz, Sumiyya Khalid, Amina Bukhari, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: The adolescent is the time period between puberty and psychophysical maturity where endocrinological, metabolic and somatic changes occur, the most frequent menstrual disorders during adolescent are; polymenorrhe, oligomenorrhea, dysmenorrhea. The present study aimed to assess the menstrual pattern and common menstrual disorders among adolescent girls. Methodology: This descriptive cross-sectional study was carried out on 75 adolescent girls in the Department of Gynecology, Sindh Government hospital Landhi from August-2021 to January 2022. All the adolescent girls with minimum and maximum menarche age of 9 years and 16 years respectively were enrolled in this study. Girls with chronic disease and hormonal use were excluded. Only already menstruating girls were asked to participate. Informed consent was taken from each participant. A self-administered structured questionnaire was used to gather information such as socioeconomic status, demographic details, contraceptive pills usage, smoking habits, and anthropometrics. The girl’s menstrual pattern was associated with menarche age, average bleeding days, weight, recent menstrual intervals, and complications such as amenorrhea, secondary amenorrhea, menorrhagia, dysmenorrhea, and premenstrual syndrome. SPSS version 25 was used for data analysis. Results: Mean age at menarche was 11.82±2.10 years with a range from 9 to 16 years. The menstrual cycles mean length was 31.6±5.8 days. The incidence of irregular menstruation, prolonged menstrual bleeding, and dysmenorrhea were 69.3% (n=52), 8% (n=6), and 22.6% (n=17) respectively. Of the total 52 irregular menstrual cycles, the prevalence of amenorrhea, oligomenorrhea, and polymenorrhea was 5.3% (n=4), 42.7% (n=32), and 21.3% (n=16) respectively. There were no significant associations found between menstrual irregularities and other factors such as age at menarche, BMI, physical activity, age, fat intake, and nutritional status. Out of 6 prolong menstrual bleeding; the incidence of medical disease, anemia, and ovarian cysts was three, two, and one case respectively. Conclusion: Our study found that irregular menstrual cycle and dysmenorrhea has higher prevalence among adolescent girls. Oligomenorrhea was the prevalent irregular menstrual problem. Irregular menstruation has no significant association with age, BMI, age at menarche, nutritional status, and physical activities. Prolong bleeding cycle was due to medical disease, anemia, and ovary cyst. Educational program and proper health information promotion should be arranged to minimize the possible consequences and complications caused by menstruation of adolescent’s girls. Also, adolescent girls should record their menstrual frequency and regular prospective after menarche to minimize these sequelae. Keywords: Menstrual Pattern, Adolescent girls, Dysmenorrhea,